Kebijakan Insentif Tax Allowance Kepada Bidang Usaha Tertentu Di Daerah Tertentu Dalam Kaitannya Dengan Asas Equity - , RANDHA TRIHATMAJA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In Government Regulation No. 52 year 2011, the Second Amendment of Government Regulation No. 1 Year 2007 on Income Tax Facilities for Investment in Certain Business Fields and in Certain Areas, the government has set 129 field of businesses. Based on the principle of accuracy and the priciple of equity, the government must act carefully in making regulations and determining which business sectors are proper for Tax Allowance incentives. Moreover, based on the principle of equity, the government is not allowed to do discrimination among taxpayers. Because, in the same situation taxpayers should be treated equally, and in different situation taxpayers should be treated differently. This study is combination of normative legal research and empirical legal research. Empirical studies conducted using interview techniques against informant, which are officers at the directorate general of taxation and finance ministry officials. Normative legal research conducted by collecting legal materials, namely materials of primary, secondary and tertiary. To get the answer of the problems (legal issues), the writer use problem-solving approach, namely approach law (Statute approach) and the conceptual approach (Conseptual Approach). The purpose of granting incentives of income tax is to provide the needed tax facilities, especially to encourage the success of economic activity sector which highly priority on national scale, to encourage business growth and improve competitiveness, to support national defense and to facilitate national development. In giving the Incentives of Tax Allowance is not fulfilled one of the horizontal equity elements, namely Equals treatment for the Equals, because the Incentives Tax Allowance give certain simplicity towards existing types of businesses. Accordingly, by just providing simplicity to certain business sectors or certain areas, the government has conduct discrimination against the taxpayers. Whereas, in the determination of 129 the fields of business. Incentives Tax Allowance recipients do not deviate the principles of accuracy. However, the government does not directly involving the entrepreneurs as one of the stakeholders. So, the entrepreneurâs opinion towards the determination of recipient business field is not heard directly and the obligation to hear in principle of accuracy not applied. Key words : law, tax, incentives, investment, tax allowance